PENDEKATAN ANTROPOLOGI DALAM STUDI ISLAM - Taufik Ismail; Muhammad Umar; Ahyarudin; Zulfi Mubaraq (Qolamuna : Jurnal Studi Islam, 2023)
Abstract : The anthropological approach in researching and studying religion can be understood as an effort to understand religion through its form of practice that grows and develops in people's lives. This study aims to discuss and examine three things, namely; A deep understanding of the anthropological approach in Islamic studies in etymology and terminology. The second examines research methods, techniques and steps with an anthropological approach. third, exploring the results of research from the implementation of anthropological approaches in Islamic studies. This research uses the library research method, which is related to the method of collecting library data sourced from 10 books and 10 related journals. The results of this study are; First, the anthropological approach in studying religion means using the methods used by the discipline of anthropology in looking at a problem in an effort to understand religion. In terms of the use of anthropological approaches to study religion. secondly, the scientific method in anthropology is:1.fact collection, 2.determination of general characteristics and systems, 3. verification. The three implementations presented in this study are two things, namely: humanism in Islam and religious celebrations of haul. Keywords : Islamic Studies, Anthropological Sciences, Society.